Compilation of the Test Load Spectrum of Wind Power Gearbox based on the Random Wind Speed Model - Xu Fang; Zhou Zhigang (Jixie chuandong, 2015)
In order to compile the load spectrum for dynamic characteristic and fatigue life test of wind turbine gear transmission system,the external random wind load is obtained on the basis of simulating reality wind speed and aerodynamics theory,and by using the rain- flow counting method and mathematical statistics method,the statistic and analysis of the input random wind load data is carried out. The relationship between the magnitude and the occurrence frequency of load and the probability distribution are obtained based on the fluctuation center method,and the eight levels test load spectrum for wind turbine transmission system is compiled.The randomness of wind speed and the bench testing are combined to make the results more in line with the actual,and a test foundation for precisely evaluate the dynamic characteristic and fatigue reliability of gear transmission system of wind turbine is provided.